2011
DOI: 10.3109/00016489.2011.615067
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic study of human vocal fold mucosa unphonated over a decade

Abstract: The vocal fold mucosae (including maculae flavae) were atrophic. The vocal fold mucosa did not have a vocal ligament, Reinke's space or a layered structure. The lamina propria appeared as a uniform structure. Morphologically, the VFSCs synthesized fewer extracellular matrices, such as fibrous protein and glycosaminoglycan. Consequently, VFSCs appeared to decrease their level of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…In the previous experimental study in rabbits, the lamina propria of the vocal fold also displayed a pronounced HA staining in the loose connective tissue of the subepithelium. 11 This is in contrast to a recent article 19 which states that there is no HA in the lamina propria of "unphonated" human vocal folds.…”
Section: Discussioncontrasting
confidence: 50%
“…In the previous experimental study in rabbits, the lamina propria of the vocal fold also displayed a pronounced HA staining in the loose connective tissue of the subepithelium. 11 This is in contrast to a recent article 19 which states that there is no HA in the lamina propria of "unphonated" human vocal folds.…”
Section: Discussioncontrasting
confidence: 50%
“…In particular, older adults had lower minimum, maximum and mean f0 and amplitude SD values compared with younger adults for sustained vowels, but similar f0 and amplitude SD values compared with younger adults for connected speech. Because speech fundamental frequency is due to the physiological characteristics of the vocal folds and control of the larynx musculature (Honjo and Isshiki 1980;Bloch and Behrman 2001;Baken 2005;Sato et al 2011), the absence of change observed in mean and range speech fundamental frequency here suggests that the state of the tissue and general motor control did not deteriorate with age (at least in the age range studied), or did not deteriorate enough to have a functional impact. These results indicate that, while sustained vowel production was affected negatively by age, connected speech was less vulnerable to age.…”
Section: Connected Speechmentioning
confidence: 75%
“…In particular, physiological changes occur in the larynx (Honjo and Isshiki 1980;Bloch and Behrman 2001;Ximenes Filho et al 2003;Kersing and Jennekens 2004;Pontes et al 2005Pontes et al , 2006Sato et al 2010Sato et al , 2011, the vocal tract (Pontes et al 2006), and the respiratory system (Linville 1996;Teles-Magalhães et al 2000;Ramig et al 2001;Sauder et al 2010). These changes include calcification and ossification of cartilages, muscles and vocal fold atrophy, vocal fold bowing (i.e., inward curve) and reduced mucosal wave, and reduced pulmonary lung pressures, volumes, elasticity, and recoil.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a human adult who never phonated past 64 years of age due to a cerebral hemorrhage, lost the ligament architecture. The vocal fold morphology returned to its infant-like state, with a uniform rather than a layered structure (Sato, Umeno, Ono, & Nakashima, 2011). From these studies it is reasoned that evolution has provided the cell structure (stellate cells at the endpoints of the vocal folds) for multiple layer development, but tissue stress from vocalization is needed to build the structure.…”
Section: Methodsmentioning
confidence: 99%